A survey of mobile cloud computing offloading concepts based on measurements and algorithms - Piramu Preethika, SK; Gobinath, R (International Journal of Engineering and Technology, 2018)
Handheld computing devices at the moment everywhere in the arms of generation dependent human beings of every age. Clients are looking for new innovative thoughts to first and best utilization of Smart Mobile Devices. The rapid enlargement of the number of clever telephone users has given rise of various research subjects. While the technological advancements are happening from hardware and package levels, novel ideas are being introduced. One amongst those ideas is Mobile Cloud computing which is the mix of cloud computing, mobile compu-ting and wireless networks to bring wealthy process resources to mobile users, network operators, yet as cloud computing suppliers. MCC offloading is a technique to overcome the barriers like battery life, memory usage, computation difficulties faced in Mobile computing with the help of cloud. This survey not only focuses on the concepts of offloading, it also concentrates on the measurements and basic ideas of Mobile Cloud computing related algorithms.Â